A Preliminary Assessment of the Potential Health and Genetic Impacts of Releasing Confiscated Passerines Into the Wild: A Reduced-Risk Approach - Cruz, Cláudio E. F.; Funkler, Gustavo R.; Zani, André L. S.; Wagner, Paulo G. C.; Andretta, Inês; Segura, Luciano N.; Fagundes, Nelson J. R. (Frontiers in Veterinary Science, 2021)
The illegal capture and trade of wild birds have long been threats to biodiversity. The rehabilitation and release of confiscated animals may be a useful conservation tool in species management. However, differences between populations regarding health (e.g. different pathogens) and adaptation (e.g. local adaptation) must be taken into account, since both can negatively impact the recipient population. In this pilot study, we used two of the most illegally trafficked Brazilian wild passerine species, namely the red-crested cardinal (Paroaria coronata) and green-winged saltator (Saltator similis) as case studies and assessed some of the health threats that the release of confiscated passerines may pose to free-living birds. We also investigated the level of difference in mitochondrial genetic structure among populations living in different ecoregions. Blood, feces, and oropharyngeal swabs from confiscated (n=115) and free-living (n=120) passerines from the release sites were tested for the Newcastle disease virus, Salmonella spp., and Mycoplasma gallisepticum. These are considered major avian diseases by the Brazilian National Avian Health Program. We analyzed mtDNA to study the difference in genetic structure between populations using samples from 127 free-living passerines. We found no evidence of the Newcastle disease virus or Salmonella spp. in confiscated or free-living passerines from either species. However, the levels of infection with M. galissepticum detected in our study for red-crested cardinals and green-winged saltators calls for a high degree of caution in captive release programs. The difference in genetic structure between populations occurring in different regions was low, and was not significant between those from the Pampa/Subtropical Grasslands region. These results suggest that it may be possible to establish a cost-effective and sensitive protocol for releasing confiscated songbirds, provided that further genome-wide studies indicate that the functional genetic diversity among (at least some of the) populations is also low.